Experimental relocation of the mitochondrial ATP9 gene to the nucleus reveals forces underlying mitochondrial genome evolution. - Maïlis Bietenhader; Alexandre Martos; Emmanuel Tetaud; Raeka S Aiyar; Carole H Sellem; Roza Kucharczyk; Sandra Clauder-Münster; Marie-France Giraud; François Godard; Bénédicte Salin; Isabelle Sagot; Julien Gagneur; et al. (PLoS Genetics)
Only a few genes remain in the mitochondrial genome retained by every eukaryotic organism that carry out essential functions and are implicated in severe diseases. Experimentally relocating these few genes to the nucleus therefore has both therapeutic and evolutionary implications. Numerous unproductive attempts have been made to do so, with a total of only 5 successes across all organisms. We have taken a novel approach to relocating mitochondrial genes that utilizes naturally nuclear versions from other organisms. We demonstrate this approach on subunit 9/c of ATP synthase, successfully relocating this gene for the first time in any organism by expressing the ATP9 genes from Podospora anserina in Saccharomyces cerevisiae. This study substantiates the role of protein structure in mitochondrial gene transfer: expression of chimeric constructs reveals that the P. anserina proteins can be correctly imported into mitochondria due to reduced hydrophobicity of the first transmembrane segment. Nuclear expression of ATP9, while permitting almost fully functional oxidative phosphorylation, perturbs many cellular properties, including cellular morphology, and activates the heat shock response. Altogether, our study establishes a novel strategy for allotopic expression of mitochondrial genes, demonstrates the complex adaptations required to relocate ATP9, and indicates a reason that this gene was only transferred to the nucleus during the evolution of multicellular organisms.